Marketing Communication Trends in MSMEs and Their Implications for Consumer Behavior: A Systematic Literature Review (2015–2025) - Hasnidar (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
: Digital marketing communications have undergone a fundamental transformation that has encouraged micro, small, and medium enterprises (MSMEs) to adopt new approaches in reaching and retaining consumers. This study aims to identify, evaluate, and synthesize scientific literature on marketing communications trends in MSMEs and their implications for consumer behavior. This study uses a Systematic Literature Review with the Prisma Method with the help of Boolean operators (AND, OR, NOT) and the Mendeley Application. This study is limited to searching only journal articles from Scopus, Web of Science, ScienceDirect, Emerald Insight, Springer, and Google Scholar, published between 2015 - 2025. A total of 30 articles met the inclusion criteria and became the basis for the synthesis in this study. The main findings show five dominant themes: (1) the evolution of marketing communications from traditional to digital and omnichannel; (2) the dominance of social media platforms, especially Instagram, TikTok, and WhatsApp Business, as the main communication channels for MSMEs; (3) the strategic role of content marketing and user-generated content in building customer engagement; (4) the significance of nano- and micro-scale influencer marketing in driving consumer trust; and (5) the significant impact of digital marketing communications on consumer trust, loyalty, and purchasing decisions. Practically, these findings provide strategic guidance for MSMEs in designing effective marketing communications in the digital era. Future research is recommended to explore the role of artificial intelligence, metaverse marketing, and hyper-personalization in the MSME context. Recent studies also indicate the growing influence of emerging technologies such as artificial intelligence (AI), marketing automation, predictive analytics, and metaverse-based consumer interactions in shaping future MSME marketing communication strategies. These developments suggest that MSMEs are increasingly moving beyond conventional social media utilization toward more personalized and data-driven marketing approaches.